Autophagy in muscle regeneration: potential therapies for myopathies. Issue 3 (17th April 2022) - Chen, Wei; Chen, Yushi; Liu, Yuxi; Wang, Xinxia
Abstract: Autophagy classically functions as a physiological process to degrade cytoplasmic components, protein aggregates, and/or organelles, as a mechanism for nutrient breakdown, and as a regulator of cellular architecture. Its biological functions include metabolic stress adaptation, stem cell differentiation, immunomodulation and diseases regulation, and so on. Current researches have proved that autophagy dysfunction may contribute to the pathogenesis of some myopathies through impairment of myofibres regeneration. Studies of autophagy inhibition also indicate the importance of autophagy in muscle regeneration, while activation of autophagy can restore muscle function in some myopathies. In this review, we aim to report the mechanisms of action of autophagy on muscle regeneration to provide relevant references for the treatment of regenerating defective myopathies by regulating autophagy. Results have shown that one key mechanism of autophagy regulating the muscle regeneration is to affect the differentiation fate of muscle stem cells (MuSCs), including quiescence maintenance, activation and differentiation. The roles of autophagy (organelle/protein degradation, energy facilitation, and/or other) vary at different myogenic stages of the repair process. When the muscle is in homeostasis, basal autophagy can maintain the quiescence state and stemness of MuSCs by renewing organelle and protein. After injury, the increased autophagy flux contributes to meet biological energy demand of MuSCs during activation and proliferation. By mitochondrial remodelling, autophagy during differentiation can promote the metabolic transformation and balance mitochondrial‐mediated apoptosis signals in myoblasts. Autophagy in mature myofibres is also essential for the degradation of necrotic myofibres, and may affect the dynamics of MuSCs by affecting the secretion spectrum of myofibres or the recruitment of supporting cells. Except for myogenic cells, autophagy also plays an important role in regulating the function of non‐myogenic cells in the muscle microenvironment, which is also essential for successful muscle recovery. Autophagy can regulate the immune microenvironment during muscle regeneration through the recruitment and polarization of macrophages, while autophagy in endothelial cells can regulate muscle regeneration in an angiogenic or angiogenesis‐independent manner. Drug or nutrition targeted autophagy has been preliminarily proved to restore muscle function in myopathies by promoting muscle regeneration, and further understanding the role and mechanism of autophagy in various cell types during muscle regeneration will enable more effective combinatorial therapeutic strategies.